Visitor satisfaction at the Gunung Anyar Mangrove Resort, Surabaya: The mediating role of perceived value on service quality, tourist attractions, and infrastructure - Zainal Abidin; Aliflamita Marstati Nur Rizky; Rian Eka Parameswari (JURNAL MINA SAINS, 2025)
Indonesia has the largest mangrove forest in the world. Surabaya City, in addition to being a center of industry and trade, also has great potential for ecotourism development and is known to have educational coastal ecotourism areas. Gunung Anyar Mangrove Botanical Garden, Surabaya, is one of the significant mangrove areas in Indonesia. The increasing popularity at KRM Gunung Anyar, Surabaya results in an increase in the number of visitors and is a challenge in itself in improving the quality of services, tourist attractions, and infrastructure to visitor satisfaction by maintaining and stabilizing visitor ratings. This study aims to analyze the effect of service quality, tourist attractions, and infrastructure on visitor satisfaction through perceived value as mediation. This research uses a quantitative descriptive approach with a sample of 150 respondents with a research instrument in the form of a questionnaire. The data analysis used is SEM WarpPLS 8.0. The results showed that service quality, and tourist attractions have a direct influence on visitor satisfaction through perceived value as mediation, while infrastructure has no direct influence. The existence of this finding shows the importance of perceived value by visitors in fulfilling visitor satisfaction which also sustainably strengthens the competitiveness of KRM Gunung Anyar, Surabaya with other tourist destinations.